Chemistry and biochemistry of molecular probes used in the detection of reactive oxygen and nitrogen species - Kalyanaraman, Balaraman (Henry Stewart Talks, 2007)
Reactive oxygen and nitrogen species play a critical role in physiological and pathological signaling processes, Because of the rapid reaction between the radicals (for example, nitric oxide and superoxide), it is very difficult to detect and quantitate the formation of these species under pathophysiological conditions, Complex interrelationship between the reactive oxygen and nitrogen species, Importance of understanding the chemistry of the fluorophores and spin traps that are often employed in the detection of these species
Archived at 2018/05/31